Mind Mapping untuk Meningkatkan Prestasi Siswa Kelas VII MTs Ar Rohman Nglaban pada Mata Pelajaran Sejarah Kebudayaan Islam - Humairo Inda Ikmalina; Zaenal Arifin Hasan (CV. Ulil Albab Corp, 2023)
By involving students in imagination exercises to organize important concepts into clear mind maps, the mind mapping teaching and learning approach has a role in improving student academic achievement. In this research, class VII students of MTs Ar Rohman Nglaban Jombang will use mind mapping to study Islamic Cultural History (SKI). The pretest-posttest control group design was used to evaluate students' scores in the experimental group (receiving treatment) and the control group (not receiving treatment) to get an overview of the relationship between the mind mapping technique and student academic achievement. The mind mapping teaching and learning approach positively increases academic achievement by involving students in imagination exercises to arrange important concepts into clear mind maps. This study uses a quantitative method with an experimental approach to examine the influence experienced by research subjects before and after receiving treatment (treatment). The results of this study indicate that the posttest results of the group that was given the treatment had a more satisfactory significance (60.67) than the group without treatment (49.11) so that the application of the mind mapping teaching method in the subject of Islamic Cultural History can improve student academic achievement.